Otomatisasi Pemberi Pakan Kura-Kura Menggunakan Fuzzy Logic Dan Base64 User Password Security Berbasis Esp8266 - Muhammad Naufal Asamukti; Septi Andryana; Ira Diana Sholihati (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
Currently, many automation systems have been implemented in various fields, one of which is animal husbandry. There are many hobbyists who want to keep turtles, both for care and for business. It is quite difficult now to be preoccupied with matters that require leaving the house. Therefore the owner must have a lot of free time to care for the turtles. In fact, keeping turtles is also not easy, there are many obstacles to face. One of them is to provide feed manually by still using human power, therefore the aim of this research is to make an automatic feeding device to make it easier for turtle keepers to provide feed automatically with a set time that can be determined. This study uses ESP8266 as a hardware platform to connect to a Wi-Fi network. In this study monitoring feed via the web and connected to the tool to be made, the author integrates ultrasonic sensors for testing based on the percentage of remaining feed that comes out, with the method used, namely Fuzzy Logic to calculate the percentage of the remaining feed that comes out. By using an ultrasonic sensor this research has been successfully carried out according to the main purpose of the research, the results of this test have been carried out and got the desired result of the author, namely 100, which means that if the feed capacity is 8cm during the day, the servo will open according to the action given, and it can be concluded that this research has been successful.